Проблемы физического воспитания школьников через призму взглядов учителя (Pedagogy of Higher and Secondary Education, 2014)
Shutko V. V. Problems of physical education in schools in the light of the views of the teacher.This paper discusses some problems of modern physical education in schools, industrial metropolis. The method of anonymous survey among teachers identified their professional capacity, level and quality of teaching the subject, the ratio of students to the knowledge bases of poor health and physical development of students.
Keywords: teacher; physical education; professionalism; physical development; tune motor activity